Sphingosine 1-Phosphate induces filopodia formation through S1P2R activation of ERM proteins - Gandy, K. Alexa Orr (2013)
Previously we demonstrated that the sphingolipids ceramide and sphingosine 1-phosphate (S1P) regulate phosphorylation of the ERM family of cytoskeletal proteins [1]. Herein, we show that exogenously applied or endogenously generated S1P (in a sphingosine kinase-dependent manner) result in significant increases in phosphorylation of ERM proteins as well as filopodia formation. Utilizing phosphomimetic and non-phosphorylatable ezrin mutants, we show that the S1P-induced cytoskeletal protrusions are dependent on ERM phosphorylation. Employing various pharmacological S1P receptor agonists and antagonists, along with small interfering RNA techniques and genetic knockout approaches, we identify the S1P Receptor 2 (S1P2R) as the specific and necessary receptor to induce phosphorylation of ERM proteins and subsequent filopodia formation. Taken together, the results demonstrate a novel mechanism by which S1P regulates cellular architecture that requires S1P2R and subsequent phosphorylation of ERM proteins.